Game Edukasi Simulasi Mitigasi Bencana Hidrometeorologi Dengan Metode Game Development Life Cycle - Hardi Saputra, Purnama; Azrino Gustalika, Muhamad; Wandala Putra, Agie (Universitas Multi Data Palembang, 2024)
Hydrometeorological disasters in Indonesia, such as floods, landslides and storms, pose serious threats to the physical, psychological safety and infrastructure of society. Learning media plays an important role in increasing society's understanding and preparedness in facing hydrometeorological disasters, especially for the younger generation who live in the technological era, where traditional learning methods are less effective. This research proposes the development of game-based learning media using the Game Development Life Cycle Method to increase literacy and involvement of the younger generation in mitigating hydrometeorological disasters. By conducting a questionnaire with 5 disaster mitigation experts or BMKG and 27 professional workers, the results obtained from Black Box Testing show that all the functionality and features contained in the game have no problems and the results of Usability Testing show a high level of ease of use of features, performance, efficiency, ease of remembering features, and satisfaction in playing are proven by an average score of 4 and the lack of errors is proven by an average score of 2.